Synthesis, Crystal Structure and Thermochemical Properties of a One-Dimensional Chain Complex [Cd（succ）PIP]n - 李霞 赵文杰 刘飞 谭金婷 冯星 卢颖莉 杨旭武 (Chinese journal of chemistry, 2012)
A new complex, [Cd（succ）PIP], （PIP=2-phenyl-imidazo[4,5-J]l,10-phenanthroline, H2-succ=succinate）, was synthesized and characterized by X-ray crystallography, elemental analysis, and TG-DTG. The results show that the complex crystallizes in an orthorhombic space group Pcca; a=14.065（2） A, b=9.901（8） A, c=28.933（2） A and Z=8. The structure of the complex is one-dimensional chain [Cd（succ）PIP],, and each Cd2＋ is five-coordinated by two chelating nitrogen atoms from one PIP ligand, three oxygen atoms from three different succ dianionic ligands to form a distorted trigonal-bipyramida geometry. The constant-volume combustion energy of the complex, AoU, was determined by an intelligent micro-rotating-bomb calorimeter （IMRBC-type I） at 298.15 K. Then the standard mo- lar enthalpy of combustion, AcHm, and the standard molar enthalpy of formation, △fHm have been calculated.